Metal-free and light-promoted radical iodotrifluoromethylation of alkenes with Togni reagent as the source of CF3 and iodine. Issue 25 (10th March 2017) - Beniazza, Redouane; Douarre, Maxime; Lastécouères, Dominique; Vincent, Jean-Marc
Abstract : Iodotrifluoromethylation of alkenes is effectively conducted by combining benzophenone, "black light", isopropanol and Togni reagent1 as the source of both the CF3 group and iodine atom. Abstract : A light-promoted methodology for the iodotrifluoromethylation of alkenes was developed. For the first time a Togni reagent was exploited as the source of both the CF3 group and iodine atom. Preliminary mechanistic studies suggest that both CF3 I and 2-iodobenzoic acid are direct sources of the iodine atom that is transferred to the products.